The Moses stone - Becker, James (Onyx, 2010)
"Called to North Africa to investigate, Detective Chris Bronson follows a trail of clues that plunge him from the hustle of a Moroccan market to the deserted caves of Qumran: from the sinister echoes of a water-filled tunnel under the city of Jerusalem to a windswept fortress whose names spells death. Threatened on every side by ruthless men with their own agendas, Bronson is plunged into a mystery that has gone unsolved since biblical times. For the stone he must find is older and far more dangerous than he could ever have imagined"--P. [4] of cover.